Characterisation of andersonite by Raman, luminescence and laser-induced breakdown spectroscopy. (July 2022) - Frankland, Victoria L.; Milodowski, Antoni E.; Read, David
Abstract: Andersonite (Na2 Ca[UO2 (CO3 )3 ]·(5+ x )(H2 O) where x ≤ 1) has been reported from oxidised, hydrothermal uranium ores, typically as efflorescent coatings on the underground walls of mine workings. It may also occur in underground repositories for spent nuclear fuels owing to the preponderance of cementitious materials used as grouts, backfill and for structural stability. Should this be the case, its high solubility would be expected to lead to enhanced uranium mobility. This study reports on the use of Raman, time-resolved luminescence and laser-induced breakdown spectroscopy to characterise andersonite; the first attempt to use all three laser-based techniques in tandem for this mineral. Well defined Raman features were observed with the resolved peaks corresponding well with previous studies, although differences were found in the number of resolvable peaks due to the low Raman signal emitted in some of the wavenumber regions selected. Seven emission and eight excitation luminescence peaks were resolved for the phase and a lifetime value of 96.8 ± 6.7 μs was extracted from luminescence decay measurements. Compositional LIBS analysis was successful in identifying minor K-bearing inclusions in the specimen, confirmed by optical and scanning electron microscopy, that were not detectable by the other methods employed. The findings indicate that multiple laser-based techniques offer the potential for real-time characterisation of uranyl phases formed in environments where intrusive sampling and 'off-site' laboratory analysis is impracticable. Graphical abstract: Image 1 Highlights: Alternative methods used where intrusive sampling and analysis are impracticable. Uranyl carbonates may be important intermediates influencing uranium mobility. First in tandem characterisation of andersonite by Raman, luminescence and LIBS. First reported luminescence excitation spectrum for andersonite.